Design of A Web-Based Teacher Payroll Information System Using CodeIgniter 4 Framework at MTs Ma’arif 30 Sumber Rejeki Mataram, Lampung - Nitami, Shella; Auliana, Sigit; Rakhim Setya Permana, Basuki (PT ARRUS Intelektual Indonesia, 2025)
In today's digital era, many educational institutions are transitioning to automated systems to support more efficient administrative processes. MTs Ma’arif 30 Sumber Rejeki Mataram Lampung, as one of these institutions, still faces several issues in managing teacher payroll, which is currently handled manually. This manual process often leads to miscalculations, delayed payments, and inaccuracies in payroll data. Therefore, an information system is needed to automate and simplify payroll data management in order to improve efficiency and accuracy. This study aims to design a Web-Based Teacher Payroll Information System using the CodeIgniter framework. The system is expected to manage payroll data more accurately, including salary calculations, allowances, deductions, and the generation of more efficient and transparent reports. The method used in this study is the Waterfall model, which consists of five main stages: requirements analysis, system design, implementation, testing, and maintenance. The results of the study show that the developed system successfully automates the payroll process, reduces calculation errors, and simplifies the generation of payroll reports that can be easily accessed by relevant parties. The conclusion of this research is that the web-based payroll information system designed can improve efficiency, transparency, and accuracy in the management of teacher salaries at MTs Ma’arif 30 Sumber Rejeki Mataram Lampung.